Anthropocentric Paradigm: Problems, Basic Concepts and Provisions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the author examines the most significant provisions of the scientific paradigm, the problems of the anthropocentric paradigm, the key concepts of interdisciplinarity and textocentrism.